Pressure transmission and distribution of different thermoplastic resin denture bases under impact load - Hubban Nasution (Chulalongkorn University, 2016)
Pressure transmission and distribution under a denture base may be different depending on the denture base materials used. The purposes of the present study were to examine the pressure transmission and distribution of thermoplastic resin denture base materials and a heat-polymerized polymethyl methacrylate (PMMA) denture base material under an impact load, and to evaluate the modulus of elasticity and nanohardness of the thermoplastic resin denture bases. Five different thermoplastic resin denture base materials (three polyamide: FRS, TCS and VAL, one polycarbonate: BPC and one ethylene propylene: DUR) and one PMMA (TRI) denture base material with a mandibular first molar acrylic resin denture tooth set in each denture base specimen (n=6) were evaluated. Pressure transmission area and maximum pressure of the specimens under an impact load of 50 N were observed using pressure sensitive sheets and digital analysis software. The modulus of elasticity and the nanohardness of the denture bases (n=10) was measured using a nanoindentation system. The pressure transmission area, modulus of elasticity and the nanohardness data were statistically analyzed using one-way ANOVA, followed by Tamhane’s post hoc multiple comparison test, whereas the nanohardness data was followed by Tukey HSD test (α = 0.05). The maximum pressure data were statistically analyzed using Kruskal-Wallis H test, followed by Mann-Whitney U test (α = 0.05). The pressure transmission area of the TCS group showed the greatest, while that of DUR showed the lowest (P < 0.05). The maximum pressure of VAL, TCS and BPC were comparable, and dramatically lower than that of TRI. All modulus of elasticity and nanohardness of all thermoplastic resin denture base material groups demonstrated lower than those of TRI (P < 0.05).